The Promoting integrity in the civil service: economic, legal and social aspects in the context of the republic of Kazakhstan (Journal of Economic Research & Business Administration, 2025)
This article examines the concept of integrity in the civil service, its significance, and approaches to its development, with a particular emphasis on the economic dimensions and the impact of integrity on the efficiency of public administration. Theoretical foundations for strengthening the principle of integrity in the civil service are analyzed, with a focus on mechanisms for its institutionalization within the public governance system of the Republic of Kazakhstan.Special attention is given to the role of a performance-based remuneration system, particularly one founded on a factor-point evaluation of civil servants, as an economic incentive for ethical behavior and improved productivity in the civil service. The article includes a comparative analysis of international experiences - specifically those of the Kingdom of Denmark and the People’s Republic of China - in shaping integrity systems through economically grounded approaches, identifying lessons applicable to Kazakhstan’s national context.Furthermore, the research explores the importance of ethical standards, transparency, and accountability in fostering institutional trust, alongside an assessment of the economic benefits of reducing corruption risks through digitalization and the implementation of e-government tools. In addition to traditional measures such as criminal prosecution, education, training, and audits, the author proposes the promotion of integrity through incentive-based mechanisms as an effective means of embedding integrity ideology in the civil service.The findings contribute to the broader discourse on the economic effectiveness of anti-corruption strategies and highlight the strategic relevance of promoting integrity within a sustainable and results-oriented public administration framework.Key words: corruption, economic impact, public service, integrity, corruption prevention, anti-corruption policy.